Inflammatory mediators in osteoarthritis: A critical review of the state-of-the-art, current prospects, and future challenges - Rahmati, Maryam; Mobasheri, Ali; Mozafari, Masoud (Bone (New York, N.Y.), 2016)
Osteoarthritis (OA) has traditionally been defined as a prototypical non-inflammatory arthropathy, but today there is compelling evidence to suggest that it has an inflammatory component. Many recent studies have shown the presence of synovitis in a large number of patients with OA and demonstrated a direct association between joint inflammation and the progression of OA. Pro-inflammatory cytokines, reactive oxygen species (ROS), nitric oxide, matrix degrading enzymes and biomechanical stress are major factors responsible for the progression of OA in synovial joints. The aim of this review is to discuss the significance of a wide range of implicated inflammatory mediators and their contribution to the progression of OA. We also discuss some of the currently available guidelines, practices, and prospects. In addition, this review argues for new innovation in methodologies and instrumentation for the non-invasive detection of inflammation in OA by modern imaging techniques. We propose that identifying early inflammatory events and targeting these alterations will help to ameliorate the major symptoms such as inflammation and pain in OA patients. [Display omitted] •There is an important link between inflammation and progression of osteoarthritis•Main inflammatory mediators are cytokines, NO, ROS and matrix degrading enzymes•Biomechanical stress can significantly increase synthesis of inflammatory mediators•Over expression of inflammatory mediators may cause gradual deterioration of tissues•Natural anti-inflammatory compounds may have some advantages over synthetic drugs